2022
DOI: 10.1037/tra0001078
|View full text |Cite
|
Sign up to set email alerts
|

From secondary traumatic stress to vicarious posttraumatic growth amid COVID-19 lockdown in Greece: The role of health care workers’ coping strategies.

Abstract: Objective: Health care workers (HCWs) are at risk for suffering negative psychological consequences of the COVID-19 pandemic, such as secondary traumatic stress symptoms (STS), as they are exposed to this traumatic experience both directly, as community residents, and indirectly, in the care of infected patients. Following vicarious exposure, positive psychological outcomes, such as vicarious posttraumatic growth (VPTG), are also likely, though they are less studied. The present study aims to examine (a) the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 40 publications
9
62
4
Order By: Relevance
“…In comparison with this present study, Cansiz et al [61] reported higher use of negative strategies, such as self-blame, substance use, emotional support and behavioural disengagement, but also higher use of planning and emotional support strategies. Studies from Canestrari et al [62] in Italy and Vera-Monge et al [63] in Spain reported lower scores for the usage of positive approach strategies and negative avoidant strategies, while a study involving Greek healthcare professionals reported higher scores for the usage of positive approach strategies and lower usage of avoidant strategies than this present study [64].…”
Section: Main Messages In Comparison With the Literaturecontrasting
confidence: 68%
See 1 more Smart Citation
“…In comparison with this present study, Cansiz et al [61] reported higher use of negative strategies, such as self-blame, substance use, emotional support and behavioural disengagement, but also higher use of planning and emotional support strategies. Studies from Canestrari et al [62] in Italy and Vera-Monge et al [63] in Spain reported lower scores for the usage of positive approach strategies and negative avoidant strategies, while a study involving Greek healthcare professionals reported higher scores for the usage of positive approach strategies and lower usage of avoidant strategies than this present study [64].…”
Section: Main Messages In Comparison With the Literaturecontrasting
confidence: 68%
“…Amongst respondents in Phase 3 of this present study there was widespread recognition that pandemic-related work responsibilities had affected respondents' quality of home life, with working from home not enabling a break from work for many of this workforce and it was noted that an emphasis should be placed on re/creating a more healthy work-life balance [68]. Overall, evidence suggests that the use of positive coping strategies are essential in reducing stressors, improving wellbeing and work-related quality of life which can then reduce burnout [64,[69][70][71].…”
Section: Main Messages In Comparison With the Literaturementioning
confidence: 99%
“…Researchers have proposed different clusters, such as problem-focused vs. emotion-focused ( Lazarus & Folkman, 1984 ), adaptive vs. maladaptive ( Meyer, 2001 ). Zuckerman and Gagne (2003) and Kalaitzaki et al (2021) have suggested that coping responses should not be a priori defined as adaptive or maladaptive, since context is significant in attributing the meaning of adaptiveness. What seems to be consistent in the relevant literature are the specific coping strategies that are most frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, research evidence about the COVID-19 outbreak, has been mainly focused on investigating the mental health and the psychological impact of healthcare professionals and the general population, as well as the socio-economic effects and the health system responses to the pandemic crisis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Data regarding nurses’ experience from the first wave of the pandemic is lacking as research in this specific area seems to be rather limited in Greece.…”
Section: Introductionmentioning
confidence: 99%